Hearth Tax Digital : beta version - British Academy - Hearth Tax Project (2021)
"Hearth taxes were levied in medieval and early modern Europe, notably in France and the Low Countries, but were not levied in the British Isles until the late seventeenth century. Following the Restoration of the Stuart monarchy in 1660, the hearth tax was levied in England and Wales from 1662 until 1689 (it continued to be collected in Ireland until the early nineteenth century). It was charged according to the number of fireplaces in dwellings, and it was collected twice each year at one shilling per hearth. It was also levied in Scotland in 1691 with collection lasting until 1695. The hearth tax provides a remarkably rich series of records on population, wealth distribution and poverty in a period of key political, social and economic change." [self-description]